2008
DOI: 10.1158/1078-0432.ccr-08-0239
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Therapeutic Response to Epidermal Growth Factor Receptor Blockade in Colorectal Cancer

Abstract: Purpose:To evaluate noninvasive molecular imaging methods as correlative biomarkers of thera-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 43 publications
6
101
1
Order By: Relevance
“…Although several factors can influence Qdot clearance, the low liver uptake of our probe could be related to passivating effects of surface PEG or hydrazinonicotinamide (29). In any case, superior binding and in vivo kinetic properties of our probe provided high-contrast tumor images that compare favorably to previous EGF-conjugated fluorophore (30)(31)(32) or Qdot (33) probes. However, scintigraphic imaging with single photon-emitting radiopharmaceuticals, compared with PET techniques, has several limitations, including lower sensitivity, resolution, and quantitative capacity.…”
Section: Discussionmentioning
confidence: 80%
“…Although several factors can influence Qdot clearance, the low liver uptake of our probe could be related to passivating effects of surface PEG or hydrazinonicotinamide (29). In any case, superior binding and in vivo kinetic properties of our probe provided high-contrast tumor images that compare favorably to previous EGF-conjugated fluorophore (30)(31)(32) or Qdot (33) probes. However, scintigraphic imaging with single photon-emitting radiopharmaceuticals, compared with PET techniques, has several limitations, including lower sensitivity, resolution, and quantitative capacity.…”
Section: Discussionmentioning
confidence: 80%
“…To our knowledge, several investigators recently used 18 F-FLT-PET to evaluate treatment response in animal models following EGFR targeted therapy such as erlotinib and cetuximab. However, those studies performed 18 F-FLT-PET at later timing than our study (25), and did not use lung cancer cell line (26) or cetuximab (27).…”
Section: Discussionmentioning
confidence: 95%
“…2) (Kovar et al, 2006). Another study with EGF800 showed that probe accumulation in tumors reflected relative EGFR expression and EGFR occupancy by cetuximab (Manning et al, 2008).…”
Section: Natural Ligand Egfmentioning
confidence: 99%